2013
DOI: 10.1089/jpm.2012.0524
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Cardiopulmonary Resuscitation Video in Advance Care Planning for Progressive Pancreas and Hepatobiliary Cancer Patients

Abstract: Background: Cardiopulmonary resuscitation (CPR) is an important advance directive (AD) topic in patients with progressive cancer; however such discussions are challenging. Objective: This study investigates whether video educational information about CPR engenders broader advance care planning (ACP) discourse. Methods: Patients with progressive pancreas or hepatobiliary cancer were randomized to an educational CPR video or a similar CPR narrative. The primary end-point was the difference in ACP documentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 31 publications
4
124
0
1
Order By: Relevance
“…Patients exposed to video decision support tools had a greater likelihood to choose comfort goals (9), greater likelihood to complete advance directive documentation (10), and were less likely to opt for cardiopulmonary resuscitation (11). A randomized controlled trial of cancer patients found that an educational video on cancer pain improved outcomes associated with the Brief Pain Inventory and the Patient Pain Questionnaire (12).…”
Section: Introductionmentioning
confidence: 99%
“…Patients exposed to video decision support tools had a greater likelihood to choose comfort goals (9), greater likelihood to complete advance directive documentation (10), and were less likely to opt for cardiopulmonary resuscitation (11). A randomized controlled trial of cancer patients found that an educational video on cancer pain improved outcomes associated with the Brief Pain Inventory and the Patient Pain Questionnaire (12).…”
Section: Introductionmentioning
confidence: 99%
“…For a subset of patients who were given a projected life expectancy of one year and indicated that they would not want CPR, the ''DNR'' order was more acceptable than ''AND.'' Instead of using different phrasing to affect the patients' choices, providers could use other methods to educate patients about EOL care-including video decision support tools 11,12 or palliative care consult teams. 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…The goals-of-care video that subjects viewed has known benefits [7,8], is 6 minutes long, and depicts the components of three broad health care categories, life-prolonging care, limited care, and comfort care. Figure 2 shows where the video fit into the interview.…”
Section: Methodsmentioning
confidence: 99%